2022
DOI: 10.1097/fjc.0000000000001197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sodium–Glucose Cotransporter 2 Inhibitors and Glucagon-like Peptide Receptor Agonists for Atrial Fibrillation in Type 2 Diabetes Mellitus: Systematic Review With Network Meta-analysis of Randomized Controlled Trials

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, these results were not consistent across all the CVOTs regarding GLP-1RAs, and the pooled meta-analysis of CVOTs (the LEADER, SUSTAIN‐6, REWIND, HARMONY, ELIXA, and PIONEER trials) showed no significant differences in the risk of incident AF between GLP1‐RA and placebo among participants with type 2 diabetes (OR 0.93; 95% CI 0.70–1.23; I 2 = 58%) [ 28 ]. Conversely, some meta-analyses indicated that GLP-1RA was associated with a lower risk of AF/AFL compared to other glucose-lowering agents in patients with type 2 diabetes [ 24 , 26 ]. These above trials are limited by AF not being a predefined and monitored endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these results were not consistent across all the CVOTs regarding GLP-1RAs, and the pooled meta-analysis of CVOTs (the LEADER, SUSTAIN‐6, REWIND, HARMONY, ELIXA, and PIONEER trials) showed no significant differences in the risk of incident AF between GLP1‐RA and placebo among participants with type 2 diabetes (OR 0.93; 95% CI 0.70–1.23; I 2 = 58%) [ 28 ]. Conversely, some meta-analyses indicated that GLP-1RA was associated with a lower risk of AF/AFL compared to other glucose-lowering agents in patients with type 2 diabetes [ 24 , 26 ]. These above trials are limited by AF not being a predefined and monitored endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…To date, direct comparisons of SGLT2i, GLP-1RA, and DPP4i regarding the risk of AF among patients with type 2 diabetes are scarce. Although a few network metaanalyses were aimed to compare the risk of incident AF between SGLT2i, GLP-1RA, and other anti-hypoglycemic agents, the above studies show conflicting results [24][25][26][27][28][29]. Also, the data from randomized and placebocontrolled studies may be incomplete because they were derived from the documentation of adverse effects and were not predefined for systematically identifying AF.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since dysrhythmia may cause contractile dysfunction and atrial blood stasis, patients with AF in turn face an elevated risk of stroke [ 29 ]. GLP-1RAs have been found to significantly reduce AF risk in patients with diabetes compared with placebo [ 30 ] and other glucose-lowering agents including metformin, sulfonylureas, and insulin [ 31 ]. The AF risk reduction by GLP-1RAs may be attributed to their protective effects on atrial electrical remodeling [ 28 ].…”
Section: Extracerebral Effects Of Glucagon-like Peptide-1 Receptor Ag...mentioning
confidence: 99%
“…What’s more, subgroup analysis based on the type of SGLT2i use, the duration of follow-up, and the type of HF did not yield any significant differences in the AF outcomes. Most of the previous meta-analysis on the relationship between SGLT2i and AF have focused on patients with diabetes mellitus and chronic kidney disease [ 34 , 35 ]. In contrast, our meta-analysis pay attention to patients with HF.…”
Section: Discussionmentioning
confidence: 99%